2020
DOI: 10.1136/jnnp-2020-324256
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of spoken word comprehension therapy in patients with chronic aphasia: a cross-over randomised controlled trial with structural imaging

Abstract: ObjectiveThe efficacy of spoken language comprehension therapies for persons with aphasia remains equivocal. We investigated the efficacy of a self-led therapy app, ‘Listen-In’, and examined the relation between brain structure and therapy response.MethodsA cross-over randomised repeated measures trial with five testing time points (12-week intervals), conducted at the university or participants' homes, captured baseline (T1), therapy (T2-T4) and maintenance (T5) effects. Participants with chronic poststroke a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Changes in auditory comprehension measured on two sub-tests of the Comprehensive Aphasia Test 79 were also not significant between Listen-In and usual care. Although not the purpose of the current review, it is notable that Fleming et al 78 also revealed structural brain changes (assessed using T1-MRI) in both white (left hemisphere) and gray matter (right hemisphere) superior temporal gyrus that correlated with therapy outcome in a sub-set of the participants (n=25). Although these effects need to be verified in a larger sample, this study provides convincing evidence that aphasia therapy changes the structure of the brain.…”
Section: Computerized Therapymentioning
confidence: 97%
See 2 more Smart Citations
“…Changes in auditory comprehension measured on two sub-tests of the Comprehensive Aphasia Test 79 were also not significant between Listen-In and usual care. Although not the purpose of the current review, it is notable that Fleming et al 78 also revealed structural brain changes (assessed using T1-MRI) in both white (left hemisphere) and gray matter (right hemisphere) superior temporal gyrus that correlated with therapy outcome in a sub-set of the participants (n=25). Although these effects need to be verified in a larger sample, this study provides convincing evidence that aphasia therapy changes the structure of the brain.…”
Section: Computerized Therapymentioning
confidence: 97%
“…A more recently completed trial by Fleming et al 78 relied on a cross-over design to study the effects of computerized therapy to improve auditory comprehension in aphasia. Using an in-house developed app (Listen-In) that targets auditory comprehension at the single word, phrase, and sentence level and is run on a computer tablet, participants (n=35) were randomized to first receive 12 weeks of self-administered Listen-In training and then 12 weeks of usual care, or vice versa.…”
Section: Computerized Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Neuro-Rehabilitation OnLine (N-ROL): description and evaluation of a group-based telerehabilitation programme for acquired brain injury Intense rehabilitation after stroke and other forms of acquired brain injury (ABI) can lead to large clinical improvements. [1][2][3] The arrival of COVID-19 in early 2020 influenced stroke presentations 4 but reduced opportunities for rehabilitation. 5 The necessity to avoid face-to-face contact and to reach as many patients with as few staff as possible led to a three-way collaboration between University College London, University College London Hospitals NHS Foundation Trust (UCLH) and SameYou charity to set up a comprehensive, multidisciplinary group-based Neuro-Rehabilitation OnLine (N-ROL) programme.…”
mentioning
confidence: 99%
“…Our first outcome measure was the Stroke Self-Efficacy Questionnaire (SSEQ), a Likert scale (0-3) questionnaire with 13 questions with good criterion validity. 6 Our second outcome measure, Neuro-Rehabilitation OnLine Outcome Measure (N-ROLOM), a novel Likert scale [1][2][3][4][5] questionnaire with seven questions for patients and two for carers/family (online supplemental appendix). The questions were constructed from themes derived from semistructured interviews with five early participants and two carers and so had good construct validity, reflecting the context (COVID-19 pandemic) in which the N-ROL programme was being delivered.…”
mentioning
confidence: 99%